Social sciences and interdisciplinary behavior : the 4th International Congress on Interdisciplinary Behavior and Social Science (ICIBSoS 2015), Kazan Federal University, Kazan, Russia, 22-23 October 2015 & Arya Duta Hotel, Jakarta, Indonesia, 07-08 November 2015 /: the 4th International Congress on Interdisciplinary Behavior and Social Science (ICIBSoS 2015), Kazan Federal University, Kazan, Russia, 22-23 October 2015 & Arya Duta Hotel, Jakarta, Indonesia, 07-08 November 2015. (2016) - Unknown
No abstract available